Učinki transkutane električne živčne stimulacije na hitrost hoje pri pacientih po možganski kapi – pregled literature - Hočevar, Jana (Rehabilitacija (Ljubljana), 2023)
Background: Decreased walking speed is common in patients after stroke. In rehabilitation, transcutaneous electrical nerve stimulation (TENS) is used to improve sensorimotor functions. The purpose of this literature review was to investigate the effects of high-frequency TENS on walking speed in patients after stroke. Methods: The literature search was performed in the PubMed, PEDro, Cochrane Library, Embase, and CINAHL databases. In addition, the reference lists of included studies were reviewed. Randomised controlled trials that investigated the effects of TENS on walking speed of patients after stroke were included in the review. Results: Five studies that used TENS at rest in subacute and/or chronic stroke patients were included. Three studies found statistically significantly greater improvement in walking speed in the group of patients with TENS followed by conventional training compared with the groups of patients with TENS alone, placebo TENS followed by conventional training, or without treatment. Conclusion: Based on the reviewed literature, it appears that TENS for at least 30 minutes followed by functional training is an effective intervention to improve walking speed in patients with chronic stroke, whereas TENS alone is not effective. High-quality studies are needed to draw firm conclusions about the effectiveness of TENS in combination with training in the subacute phase after stroke.
Keywords: Gait; gait speed; hitrost hoje; hoja; možganska kap; Stroke; Transcutaneous Electric Nerve Stimulation; transcutaneous electrical nerve stimulation; transkutana električna živčna stimulacija